Understanding how primary care practitioners perceive an online intervention for the management of hypertension - Bradbury, Katherine (BMC Med Inform Decis Mak, 2017)
BACKGROUND: In order to achieve successful implementation an intervention needs to be acceptable and feasible to its users and must overcome barriers to behaviour change. The Person-Based Approach can help intervention developers to improve their interventions to ensure more successful implementation. This study provides an example of using the Person-Based Approach to refine a digital intervention for hypertension (HOME BP). METHODS: Our Person-Based Approach involved conducting qualitative focus groups with practice staff to explore their perceptions of HOME BP and to identify any potential barriers to implementation of the HOME BP procedures. We took an iterative approach moving between data collection, analysis and modifications to the HOME BP intervention, followed by further data collection. The data was analysed using thematic analysis. RESULTS: Many aspects of HOME BP appeared to be acceptable, persuasive and feasible to implement. Practitioners perceived benefits in using HOME BP, including that it could empower patients to self-manage their health, potentially overcome clinical inertia around prescribing medication and save both the patient and practitioner time. However, practitioners also had some concerns. Some practitioners were concerned about the accuracy of patients’ home blood pressure readings, or the potential for home monitoring to cause patients anxiety and therefore increase consultations. Some GPs lacked confidence in choosing multiple medication changes, or had concerns about unanticipated drug interactions. A few nurses were concerned that the model of patient support they were asked to provide was not consistent with their perceived role. Modifications were made to the intervention based on this feedback, which appeared to help overcome practitioners’ concerns and improve the acceptability and feasibility of the intervention. CONCLUSIONS: This paper provides a detailed example of using the Person-Based Approach to refine HOME BP, demonstrating how we improved the acceptability and feasibility of HOME BP based on feedback from practice staff. This demonstration may be useful to others developing digital interventions.